2015
DOI: 10.1016/j.peptides.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

ML-18 is a non-peptide bombesin receptor subtype-3 antagonist which inhibits lung cancer growth

Abstract: Bombesin receptor subtype (BRS)-3 is a G protein coupled receptor (GPCR) for the bombesin (BB)-family of peptides. BRS-3 is an orphan GPCR and little is known of its physiological role due to the lack of specific agonists and antagonists. PD168368 is a nonpeptide antagonist for the neuromedin B (NMB) receptor (R) whereas PD176252 is a nonpeptide antagonist for the gastrin releasing peptide (GRP) R and NMBR but not BRS-3. Here nonpeptide analogs of PD176252 e.g. the S-enantiomer ML-18, and the R-enantiomer, EMY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 38 publications
(42 reference statements)
4
32
0
Order By: Relevance
“…Transactivation of the EGFR by GRPR and NMBR, has been shown to be an important signaling cascade mediating growth effects of these receptors on a number of different neoplasms including cancers of the lung (especially nonsmall cell tumors), head and neck squamous cells, neuroendocrine cells and the prostate[8,17,37,52,5658,6062]. Studies with BRS-3 in this area are more limited, although recently a number of studies of BRS-3 growth stimulatory effects in lung cancer cells report a similar mechanism with its growth stimulatory effects occurring primarily via EGFR transactivation[53,57]. In a number of studies the transactivation of EGFR by BRS-3 and the other mammalian BnRs has been shown to involve activation of phospholipase C, Src kinases, stimulation of matrix metalloproteinases and shedding of EGF-related ligands, as well as the stimulation of reactive oxygen species[8,9,17,52,54,57].…”
Section: Brs-3 and The Mammalian Bnr Family (Table 1)mentioning
confidence: 99%
See 3 more Smart Citations
“…Transactivation of the EGFR by GRPR and NMBR, has been shown to be an important signaling cascade mediating growth effects of these receptors on a number of different neoplasms including cancers of the lung (especially nonsmall cell tumors), head and neck squamous cells, neuroendocrine cells and the prostate[8,17,37,52,5658,6062]. Studies with BRS-3 in this area are more limited, although recently a number of studies of BRS-3 growth stimulatory effects in lung cancer cells report a similar mechanism with its growth stimulatory effects occurring primarily via EGFR transactivation[53,57]. In a number of studies the transactivation of EGFR by BRS-3 and the other mammalian BnRs has been shown to involve activation of phospholipase C, Src kinases, stimulation of matrix metalloproteinases and shedding of EGF-related ligands, as well as the stimulation of reactive oxygen species[8,9,17,52,54,57].…”
Section: Brs-3 and The Mammalian Bnr Family (Table 1)mentioning
confidence: 99%
“…Two different BRS-3 antagonists have recently been described: ML-18[53] is a peptoid(S-enantiomer of PD176252, a GRP preferring antagonist[89,99]) and the other is a peptide antagonist, Bantag-1(Table 2)[31,34]. ML-18 has both a low affinity and low (<5-fold) selectivity for hBRS-3 over GRPR or NMBR (Table 2)[53].…”
Section: Brs-3 and The Mammalian Bnr Family (Table 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…This has occurred because its native ligand is unknown, it has low affinity for all natural Bn peptides, and unlike BB 2 or BB 1 receptor, for which numerous selective agonists and antagonists are described [2,6–11], until recently no agonist or antagonist with sufficient selectivity to be useful for in vivo studies, existed for BB 3 receptor [2,3,1217]. A high affinity BB 3 receptor agonist has been described, [D-Tyr 6 , β-Ala 11 , Phe 13 , Nle 14 ]Bn(6–14) (peptide #1), which allowed studies of BB 3 receptor’s signaling cascades, demonstrating it was coupled to phospholipase C, A2 and D activation as well as tyrosine kinase cascades [4,14,18–21]. However, peptide #1 was not useful for pharmacological/pathological studies because it was nonselective, having high affinity for BB 2 receptor / BB 1 receptor in all species [12,2224], as well as human BB 3 receptor [25–27], but not rat/mouse BB 3 receptor [27,28].…”
Section: Introductionmentioning
confidence: 99%